Self-Assembled Peptide Nanofibers Encapsulated with Superfine Silver Nanoparticles via Ag⁺ Coordination - Hu, Yuanyuan (Langmuir : the ACS journal of surfaces and colloids, 2015)
We demonstrate that a glutanthione-based oligopeptide, Fmoc-GCE, could self-assemble into nanofibers induced by Ag(+) ions in NaOH solution. During the self-assembly process, the superfine silver nanoparticles were in situ produced on the nanofibers. On the basis of a series of characterizations, we proposed the possible mechanism of the self-assembly, for which the coordination interaction between Fmoc-GCE and Ag(+) ions as well as the π-π stacking of fluorenyl groups were the main driving forces of the self-assembled nanofibers. At appropriate compositions, the 3D networks of Fmoc-GCE/NaOH/Ag(+) nanofibers could further form metallogel, which was responsive to pyridine and melamine, which could coordination with Ag(+) ions. Moreover, the nanofibers encapsulated with superfine silver nanoparticles exhibited catalytic ability in degradation of the azo dye and the antibacterial properties to both Gram negative (E. coli) and Gram positive (S. aureus) bacteria